A Comparative Study on the Influencing Factors of Sino-US Trade Transactions from a Longitudinal Perspective Based on Principal Component Analysis - Wu, Meiyu (Transactions on Economics, Business and Management Research, 2024)
The restructuring of relations between the two global powers, China and the US, is one of the dominant elements in today's dynamic world. However, in recent years, with the intensification of mutual strategic contradictions, the restructuring of Sino-US economic and trade relations has increasingly become a consensus among all parties. In view of this, this thesis divides the Sino-US trade friction into three stages from 2002 to 2017, from 2018 to 2020 and from 2021 to 2023, and proposes a research model based on the influence factors of China-US trade exchanges based on the principal component analysis under each timeframe. Firstly, 17 tertiary indicators are selected as the influencing factors of China-US trade exchanges, and secondly, the Pearson's coefficient correlation is utilized to screen the indicators. Next, by using principal component analysis, multiple influencing factors were downscaled into 1 and 2 principal components. GDP per capita, the exchange rate of the RMB to the US dollar, the amount of Chinese OFDI in the US, and the US import/export surplus (deficit) in trade with China are identified as the crucial factors affecting the US-China trade exchange in the three time periods.